The Impact of Conventional and Alternative Nicotine Delivery Systems on the Pathogenesis of Periodontal Diseases and Periodontal Treatment Outcomes – A Literature Review - Czerepak, Gabriela; Jędras, Aleksandra; Bednarz, Katarzyna; Pociask, Weronika; Gliwa, Katarzyna; Czajkowska, Weronika; Zowczak, Wiktoria (Quality in Sport, 2026)
Introduction: Periodontal diseases constitute a significant public health concern, and their development and progression are strongly influenced by environmental factors, including nicotine exposure. In recent years, the popularity of alternative nicotine delivery systems, such as electronic cigarettes and heated tobacco products, has increased considerably, necessitating an evaluation of their impact on periodontal tissues. Aim: The aim of this review was to compare the effects of conventional tobacco smoking and alternative nicotine delivery systems on the pathogenesis of periodontal diseases and on the outcomes of periodontal treatment. Material and Methods: A narrative literature review covering the years 2020–2025 was conducted using the PubMed, Scopus, and Google Scholar databases. Clinical studies, systematic reviews, and meta-analyses investigating the effects of nicotine on periodontal tissues and periodontal treatment outcomes were included. Results: Conventional tobacco smoking exerts a strong multidirectional effect on periodontal tissues, leading to microcirculatory disturbances, impairment of the immune response, and exacerbation of inflammatory processes, resulting in disease progression and poorer treatment outcomes. Although alternative nicotine delivery systems eliminate the combustion process, they also demonstrate adverse biological effects, including oxidative stress, microbial dysbiosis, and chronic low-grade inflammation. Their clinical impact appears to be less pronounced, yet still significant. Conclusions: No form of nicotine delivery is neutral with respect to periodontal health. Patients using both conventional and alternative nicotine products should be regarded as a group at increased risk for periodontal disease. Complete nicotine abstinence remains the most effective strategy for improving periodontal treatment prognosis.